Vein-type similar uranium deposits of Argentina. Summary information - Stipanicic, Pedro N.; Olsen, Hugo; Antonietti, C. E. M.; Berizzo, J.; Valdiviezo, Alberto (International Atomic Energy Agency, 1982)
Fil: Stipanicic, Pedro N. Comisión Nacional de Energía Atómica; Argentina